Clinical Legal Education in Latin America: Toward Public Interest (2011)
"This chapter describes key aspects of the history of clinical legal education in Latin America, which began in the 1960s, and the evolution of new approaches to clinical education in the region. It also explains the influence of the ""First Generation"" and ""Second Generation"" of the Law and Development Movement on the Latin American clinical movement, and the emergence of clinical programs based on the ideological and practical tenants of Public Interest Law (PIL). It explains further that while PIL clinics have been particularly fertile in proposing new forms of judicial intervention -they have just recently started to think more consciously about the limits of these strategies and the necessity to reconsider their role in both legal education and professional practice. The chapter then examines these developments from the perspective of four countries in the region with substantial clinical experience: Argentina, Chile, Colombia, and Mexico. © 2011 by Oxford University Press, Inc. All rights reserved."